Interprofessional education with medical and midwifery students: a prospective evaluation. - Kitson-Reynolds, Ellen; Polack, Clare; Connell, Bethany; Kermack, Alexandra J; Kelly, Emer (British Journal of Midwifery, 2025)
Background/Aims: Interprofessional working is essential for safe, high-quality obstetric and midwifery care. This study aimed to design, implement and test an interprofessional education activity bringing together two healthcare professions at the University of Southampton to explore opportunities for students' learning and problem solving. Methods: Methods A total of 30 student midwives and four rotations of 70 medical students attended a 1-hour facilitated online education activity (four total) and completed an online evaluation. Results: Overall, 16 of the 86 students positively evaluated the activities, valuing the chance to learn about each other's profession and sharing knowledge through small group discussions. Conclusions: Interprofessional education supports learners through reflective practice to consider differences in professional scope and responsibilities essential in obstetric and midwifery care. Implications for practice: Future enhancements to existing curricula could include a year-long clinical case study as well as half-day simulations. Students could present their experiences via an interprofessional case conference at the end of the year.